An administrator's guide to online education - Shelton, Kaye; Saltsman, George (USDLA book series on distance learning., 2005)
An Administrator's Guide to Online Education is an essential resource for the higher education administrator. Unlike most books regarding online education, this book is not about teaching; it is about effectively administrating an online education program. Grounded in existing distance education theory, and drawing from best practices, current research, and an extensive review of current literature, An Administrator's Guide to Online Education systematically identifies and discusses seven key issues that affect the practice of online education today: leadership and strategic planning, policy and operation, faculty, online student services, online student success, technology and the courseware management system, and finally marketing. Throughout the text, the authors provide case studies, examples, policies, and resources from actual institutions, which further enhance the value of this text. An Administrator's Guide to Online Education, encompasses the issues and provides information on how to accomplish one specific task: successful online education administration.